A Survey Report on Various Non-Invasive Glucose Monitoring Methods - et. al., Vinothini, (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Diabetes is a disease which can cause death sometimes. Long ago diabetes was very rare, only few people suffered with diabetes. But, Nowadays due to huge changes in our lifestyle, food, it is found that more number of people are suffering from Diabetes mellitus irrespective of the age. Even children during the time of birth itself they are carrying diabetes. Diabetes mellitus causes when our body does not produce adequate amount of insulin or sometimes it uses its own insulin which in turn increases blood glucose level in our body. With purpose to measure the glucose level in our blood, mostly invasive methods are employed in old days which involve tearing up the skin, introducing instruments inside the body to draw the blood to measure glucose level. Those methods may be painful and not suitable for children, much later non-invasive glucose monitoring methods introduced, which does not need to tear up the skin, it will measure glucose level without drawing the blood from the body. There are many such methods available, each one of them uses various bio signals from our body to measure the glucose level. In this paper, let us discuss about various non invasive glucose methods.